EFEKTIVITAS TEKNIK OBJEK LANGSUNG BERBANTUAN MEDIA MUSIK DALAM PEMBELAJARAN MENULIS PUISI KELAS X FASE E SMA NEGERI 5 MUKOMUKO - Enta Okta Sari; Silvia Marni; Trisna Helada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low ability to understand the elements of writing poetry. Students have difficulty finding ideas for composing sentences in writing poetry. The purpose of this study is for students to be able to describe the effectiveness of direct object techniques assisted by music media for class X phase E of SMA Negeri 5 Muomuko. This type of research is quantitative research using a pre-experimental method with a One Group Protest-Postest Design research design. The results of this study. First, the ability to write poetry before using direct object techniques assisted by music media for class X phase E of SMA Negeri 5 Mukomuko is in the range of 55-65% with sufficient qualifications by obtaining a score of 63.60. Second, the ability to write poetry after using direct object techniques assisted by music media is in the range of 66-75% with more than sufficient qualifications by obtaining a score of 70.12. In the application of direct object techniques assisted by music media, students are good in mastering the indicators of poetry elements. Third, the effectiveness of the direct object technique assisted by music media in learning to write poetry for class X phase E of SMA Negeri 5 Mukomuko. Based on the t-test, it can be concluded that the hypothesis in this study H1 is accepted and H0 is rejected. At a significant level of 95% with dk = n-1 because t count> t table (2.97> 1.70), while the N-gain score test obtained was 0.17 with low criteria. After that, the N-gain % test obtained a result of 17.91% with an interpretation of ineffective. So it can be said that the use of the direct object technique assisted by music media is not effective on the poetry writing ability of class X phase E of SMA Negeri 5 Mukomuko. But the results of the study on the ability to write poetry after using the direct object technique assisted by music media for class X Phase E of SMA Negeri 5 Mukomuko is higher than the ability to write poetry before using the direct object technique assisted by music media for class X Phase E of SMA Negeri 5 Mukomuko.